Research networking - Dzulkarnain, Ahmad Aidil Arafat (2016)
According to the World Bank, most of the developing countries including Malaysia have relatively low expenditure on research and development (R&D). The gross domestic product (GDP) for research and development in developing countries are less than 0.3% as compared to the developed nations at the percentage of more than 4%. This GDP indicator include all expenditures and investments for R & D by the government, private and other sectors in Malaysia. This GDP indicator would also consider any research and developments activities that being funded from overseas, joint research activities between local and overseas institutions/agencies and domestic funding awarded by the local industries. Collaborative researches with overseas agencies and the local industries, is one of the potential mechanisms that may increase Malaysia GDP R & D indicator for future. To our knowledge, the number of staff in Kulliyyah of Allied Health Sciences that involve in external collaborations are still low and therefore the aims of this talk are (i) to share the benefit of external collaborations (ii) to share possible ways to enhance collaborations with various parties (iii) to share various ways of registering collaborative works with IIUM for Malaysia Research Assessment Instrument (MyRA) exercise.